2015
DOI: 10.5539/ijef.v7n12p11
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Essay to Explain the Contrarian Profits in the Tunisian Stock Market: Behavioral Approach vs. Rational Approach

Abstract: This paper aims to investigate the behavioral and the rational explanations for the contrarian profits in the Tunisian stock market. We use the CAPM and the three-factor model of French (1993, 1996) to examine the rational explanations including the market risk, the size effect and the book to market effect. Behavioral explanations include the overconfidence bias and the investor sentiment. We use the decomposition of the trading volume advanced by Chuang and Lee (2006) to extract the factor reflecting the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
1
0
0
Order By: Relevance
“…The long term reversal (for 2 years) finding seems to be robust since it holds for the three industries. This is consistent with the findings of Boussaidi (2015) in the Tunisian stock market who found that such a reversal seems to be explained by a multidimensional risk including the market risk, the firms' size and the book to market, in addition to the overconfidence bias. However, for one year horizon, only the manufacturing industry displays a return reversal, while the financial and services industries displays a momentum effect.…”
Section: Determinants Of the Unrealized Capital Gains/lossessupporting
confidence: 81%
“…The long term reversal (for 2 years) finding seems to be robust since it holds for the three industries. This is consistent with the findings of Boussaidi (2015) in the Tunisian stock market who found that such a reversal seems to be explained by a multidimensional risk including the market risk, the firms' size and the book to market, in addition to the overconfidence bias. However, for one year horizon, only the manufacturing industry displays a return reversal, while the financial and services industries displays a momentum effect.…”
Section: Determinants Of the Unrealized Capital Gains/lossessupporting
confidence: 81%